Applied Strategic Foresight – Learnings from Trend Transfer at SIX - Birte Karoline Manke; Tobias Alexander Lehmann; Michael Katz (Marketing Review St.Gallen, 2020)
How to translate trends into action? Trend research yields important insights into the future development of markets. Translating possible trends into implementable use cases at different levels of the organization is, however, far from trivial. Based on a case study of SIX, one of the biggest financial service providers in Switzerland, we propose a scenario building method that we called "Pictures of the Future" to start the trend translation process.
Keywords: 650